Institutionalizing Elites : Political Elite Formation and Change in the KwaZulu-Natal Provincial Legislature. - Francis, Suzanne, 1970- (Afrika-Studiecentrum series, 2011)
This book offers a new framework for the study of political elites and an empirically rich interrogation of the realization, accumulation and exercise of institutionalized political power by political elites in the African context of the Provincial Legislature of KwaZulu-Natal.